Computational mechanics modelling of carbon nanotube-based nanocomposites - Rahmandoust, Moones (2012)
Composites are engineered materials that consist of two or more insoluble phases combined together; a continuous phase, known as the matrix, as well as interdispersed component known as the reinforcing phases. If at least one of the constituent phases of a composite material is less than 100 nm in size, e.g. the reinforcing phase, this composite is commonly termed nanocomposite. Among all the variety of different fillers that can be used as a nanocomposite’s reinforcing phase, carbon nanotubes (CNTs), have shown to be promising candidates for their very specific and remarkable mechanical and physical properties. Carbon nanotube–based nanocomposites, i.e. composite materials in which carbon nanotubes are used as the composite’s reinforcing phase, are therefore very much interesting for scientists and scholars, for the many outstanding applications that they can contribute to the world of science and industry. This study uses a computational mechanics approach to numerically characterise the properties of single– and multi–walled carbon nanotubes by simulating their molecular structure, by the finite element method, at the first stage. Special emphasis is given to investigate the effect of some imperfections in the structure of both single– and multi–walled CNTs on their mechanical properties, namely perturbation, missing atoms and silicon doping in the structure of CNTs. Later on, a unit cell of a composite material, consisting of a single CNT and its surrounding matrix is simulated and studied and finally, parallel CNTs, as reinforcement fibres in a macroscopic polymer matrix, are randomly distributed and modelled to obtain the mechanical properties of the structure and observe how random distribution of short fibres influences the properties of nanocomposites. Based on the results of this research, any type of imperfection in the structure of carbon nanotubes and carbon nanotube-based nanocomposites leads to a Young's modulus value of less than 1TPa.